Establishment of an in vitro system representing the chicken gut-associated lymphoid tissue. - Noorjahan Banu Alitheen; Susan Jane McClure; Swee Keong Yeap; Ye Wen Kristeen-Teo; Sheau Wei Tan; Peter McCullagh (PLoS ONE, 2012)
The bursa of Fabricius is critical for B cell development and differentiation in chick embryos. This study describes the production in vitro, from dissociated cell suspensions, of cellular agglomerates with functional similarities to the chicken bursa. Co-cultivation of epithelial and lymphoid cells obtained from embryos at the appropriate developmental stage regularly led to agglomerate formation within 48 hours. These agglomerates resembled bursal tissue in having lymphoid clusters overlaid by well organized epithelium. Whereas lymphocytes within agglomerates were predominantly Bu-1a(+), a majority of those emigrating onto the supporting membrane were Bu-1a(-) and IgM(+). Both agglomerates and emigrant cells expressed activation-induced deaminase with levels increasing after 24 hours. Emigrating cells were actively proliferating at a rate in excess of both the starting cell population and the population of cells remaining in agglomerates. The potential usefulness of this system for investigating the response of bursal tissue to avian Newcastle disease virus (strain AF2240) was examined.